Salsolinol modulation of dopamine neurons - Xie, Guiqin; Krnjevic, Kresimir; Ye, Jiang H. (Frontiers in Behavioral Neuroscience, 2013)
Salsolinol, a tetrahydroisoquinoline present in the human and rat brains, is the condensation product of dopamine and acetaldehyde, the first metabolite of ethanol. Previous evidence obtained in vivo links salsolinol with the mesolimbic dopaminergic system: salsolinol is self-administered into the posterior of the ventral tegmental area (pVTA) of rats; intra-VTA administration of salsolinol induces a strong conditional place preference and increases dopamine release in the nucleus accumbens. However, the underlying neuronal mechanisms are unclear. Here we present an overview of some of the recent research on this topic. Electrophysiological studies reveal that dopaminergic neurons in the posterior ventral tegmental area (pVTA) are a target of salsolinol. In acute brain slices from rats, salsolinol increases the excitability and accelerates the ongoing firing of dopamine neurons in the pVTA. Intriguingly, this action of salsolinol involves multiple pre- and post-synaptic mechanisms, including: (a) depolarizing the membrane potential of dopamine neurons; (b) activating mu opioid receptors on the GABAergic inputs to dopamine neurons, which decreases GABAergic activity and dopamine neurons are disinhibited; and (c) enhancing presynaptic glutamatergic transmission onto dopamine neurons via activation of dopamine type 1 receptors, probably situated on the glutamatergic terminals. These novel mechanisms may contribute to the rewarding/reinforcing properties of salsolinol observed in vivo.